New insights into conditional cooperation and punishment from a strategy method experiment - Stephen L. Cheung (Institute for the Study of Labor (IZA), 2011)
This paper introduces new experimental designs to enrich understanding of conditional cooperation and punishment in public good games. The key to these methods is to elicit complete contribution or punishment profiles using the strategy method. It is found that the selfish bias in conditional cooperation is made significantly worse when other players contribute more unequally. Contingent punishment strategies are found to increase with decreasing contributions by the target player and also increasing contributions by a third player. Antisocial punishments are not directed specifically toward high contributors, but may be motivated by pre-emptive retaliation against punishment a player expects to incur.
urn:nbn:de:101:1-201105173253
Keywords: C72; C91; D70; H41; 330; conditional cooperation; selfish bias; punishment; public good experiment; strategy method